KKS BERBASIS BB UNTUK MENINGKATKAN PEMAHAMAN SISWA KELAS X PADA APLIKASI TRIGONOMETRI DI SMA 02 DIPONEGORO WULUHAN JEMBER - Abd. Rohman S; Sholahudin Al ‘Ayubi (FKIP Universitas Islam Jember, 2014)
In accordance with the previous information, a few research problems emerged: (1) how is the implementation of using cooperative, contextual, and sorogan (KKS) shadow-based in enhancing students understanding of Trigonometry concept?; and (2) how can cooperative, contextual, and sorogan (KKS) shadow-based enhance the students of class X of SMA 02 Diponegoro Wuluhan Jember in understanding Trigonometry concept?. Moreover, the aimsof this study are: (1) to describe how the implementation of using cooperative, contextual, and sorogan (KKS) shadow-based in enhancing students understanding of Trigonometry concept; and (2) how cooperative, contextual, and sorogan (KKS) shadow-based can enhance the students of class X of SMA 02 DiponegoroWuluhanJember in understanding Trigonometry concept. In conducting this research, the researcher used Classroom Action Research (CAR) as research method. The data analysis started when gathering the all required data intensively. The process of data analysis is based on the steps of data analysis as employed in qualitative inquiry; (1) data reduction, (2) presenting the data, and (3) data verification. The findings are: (a) the teacher delivered the material, the concept of Trygonometry such as sin, cos, and tangent, (b) the teacher divided students into several groups, (c) the students learnt together outside the class, (d) the students, by turns, submitted their work to the teacher (sorogan), (e) the teacher checked, revised, and comment their students’ work, (f) teacher evaluated the students’ work in the classroom, (h) teacher gave the test to measure the students’ understandings about this concept, the application of Trigonometry concept, and lastly, (i) teacher rewarded the students. From the result of pre-interview with the students, it shows that they did not understand the application of Trigonometry. Whereas, the test result after applying KKS method indicated that the students’ scores are above The Criterion of Minimum Completeness (KKM).Keywords: Cooperative, Contextual, Sorogan, Shadow-based, Trigonometry